2020
DOI: 10.1155/2020/8964673
|View full text |Cite
|
Sign up to set email alerts
|

History of Prostatitis Is an Independent Risk Factor for Erectile Dysfunction: A Cross-Sectional Study

Abstract: Purpose. To determine the role of history of prostatitis (HP) as an independent risk factor for erectile dysfunction (ED) in Chinese adult males. Methods. We conducted an online survey using a crowd-sourced questionnaire in Chinese adult males. The participants were separated into two groups as adult participants with HP and with no history of prostatitis (NHP) according to the medical history record. As diagnosis criteria of ED, we used the 5 questions of the International Index for Erectile Function (IIEF-5)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
(32 reference statements)
1
8
0
Order By: Relevance
“…Therefore, the prostate volume of patients with benign prostatic hyperplasia ED is very important, because the treatment of one disease may affect other disease, and vice versa. In addition, we also found that the history of prostatitis is also an independent risk factor for ED (11).…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Therefore, the prostate volume of patients with benign prostatic hyperplasia ED is very important, because the treatment of one disease may affect other disease, and vice versa. In addition, we also found that the history of prostatitis is also an independent risk factor for ED (11).…”
Section: Introductionsupporting
confidence: 65%
“…Word analysis can show the concepts where a particular study focuses on. In our study, keywords co-occurrence analysis showed that the highfrequency keywords were mainly erectile dysfunction, men, prostate cancer, quality-of-life, radical prostatectomy, sexual function, cancer, impotence, dysfunction and outcomes, etc., indicating that the research focused on the impact on ED due to various types of prostate diseases (9,11,(24)(25)(26). The majorities of these keywords were located in the middle of the network and were important as core words as they reflect the areas of interest in this field of research.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 9 In many web survey studies, the IIEF-5 has been used as the crucial means of diagnosing ED. 46 , 47 However, several studies have found that the specificity of the IIEF-5 among the PE population is concerning. 34 , 35 , 36 …”
Section: Discussionmentioning
confidence: 99%
“…And men with ED had a possibility of previous CP/CPPS diagnosis three times more than control patients (Chung et al, 2012). Although epidemiological link between ED and CP/CPPS has been revealed, it isn't enough to explain their pathological relationship based on the current studies (Ma et al, 2020). Shoskes et al (2011) found that men with CP/CPPS tend to have evidence of greater endothelial dysfunction and arterial stiffness.…”
Section: Introductionmentioning
confidence: 89%